2019
DOI: 10.3390/nu11071560
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women in Four Low-Middle Income Countries Have a High Prevalence of Inadequate Dietary Intakes That Are Improved by Dietary Diversity

Abstract: Background: Up-to-date dietary data are required to understand the diverse nutritional challenges of pregnant women living in low-middle income countries (LMIC). To that end, dietary data were collected from 1st trimester pregnant women in rural areas of Guatemala, India, Pakistan, and Democratic Republic of the Congo (DRC) participating in a maternal lipid-based nutrient supplement (LNS) Randomized Controlled Trial to examine dietary diversity (DD), usual group energy and nutrient intakes, and prevalence of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 43 publications
5
77
0
7
Order By: Relevance
“…Participants were encouraged to consume this second supplement but the actual amount was left to the woman's discretion in order to minimize interference with consumption of the habitual diet. That this guideline was effective for Arm 1 was indicated by the lack of any difference in energy consumption from local food between Arms 1 and 2 during the first trimester in a random subsample (27). Despite provision of the protein-energy supplement, the average gestational weight gain through 32 wk remained low relative to international recommendations (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were encouraged to consume this second supplement but the actual amount was left to the woman's discretion in order to minimize interference with consumption of the habitual diet. That this guideline was effective for Arm 1 was indicated by the lack of any difference in energy consumption from local food between Arms 1 and 2 during the first trimester in a random subsample (27). Despite provision of the protein-energy supplement, the average gestational weight gain through 32 wk remained low relative to international recommendations (40).…”
Section: Discussionmentioning
confidence: 99%
“…No women were excluded on the basis of height, weight, or BMI (kg/m 2 ). Diets were predominantly based on staple foods, including grains and tubers, and were generally low in dietary diversity (27).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Lander et al [44] reported that four-fifths of rural Pakistani women in the same district (Thatta) were found to consume a diet with inadequate diversity, which might make WRA susceptible to anemia in Thatta district [44]. Dietary intake data from a similar study also indicated rural Pakistani women had the lowest mean intake of calories, protein and key micronutrients [44]. In addition to inadequate dietary diversity, the use of smokeless tobacco, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inadequate intake of iron, predominantly caused by reduced access to heme iron, which is primarily found in meat and is highly bioavailable, can contribute to iron deficiency [ 41 43 ]. Furthermore, Lander et al [ 44 ] reported that four-fifths of rural Pakistani women in the same district (Thatta) were found to consume a diet with inadequate diversity, which might make WRA susceptible to anemia in Thatta district [ 44 ]. Dietary intake data from a similar study also indicated rural Pakistani women had the lowest mean intake of calories, protein and key micronutrients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This correlates with the fact that adequate dietary diversity indicates that significantly higher intakes of most key nutrients are consumed and available for the body to maintain a normal nutritional status. 42 Number of meals consumed per day was not associated with the nutritional status of the adolescents. This agrees with some other studies which have demonstrated that no of meals does not affect weight status but contrasts the findings in a similar study in Saudi-Arabia where 13.0% of those who consumed more than four meals per day were overweight and obese.…”
Section: Discussionmentioning
confidence: 87%